Profile of The Implementation of Online Learning Assessment in Elementary School - Dina Nisatul Ilmi; Puri Selfi Cholifah; Yulia Linguistika (Universitas Negeri Malang, 2022)
This study aims to describe the implementation of the online learning assessment at SDN Kiduldalem 1 Bangil, Pasuruan Regency, along with the obstacles and difficulties in its implementation. This study used a descriptive qualitative design. The study subjects were teachers in grades 1 to 6 at SDN Kiduldalem 1 Bangil. Observation, interviews, and documentation were used in this research as data collection tools. The validity of the research was carried out with the extension of research, triangulation of techniques, and member checks. The results showed that all teachers could carry out cognitive assessments during online learning. Most of the teachers have already conducted the affective and psychomotor assessments. The obstacles and difficulties experienced in implementing learning assessments are the teachers have difficulty observing student attitudes, and preparing lesson plans and materials for online learning.